Business Ecosystem as Key for Indonesian Economic - Rizki Ramadhana (Institut Teknologi Sepuluh Nopember, 2023)
Business Ecosystem are utilized to depict how financial communities work. Business Ecosystem contains large comprise of businesses and all their partners. A part of inquire about has talked about Business Ecosystem for existing businesses. In any case, exceptionally a little, has been talked about almost how to construct and create a Business Ecosystem for new companies. New companies in Indonesia have entered the